Lycopene carotenogenesis and function in the haloarchaeon Haloferax volcanii - Russell, Daniel John (2013)
The halophilic archaeon Haloferax volcanii is a carotenogenic organism, native to the dead sea. Its carotenogeneic pathway was characterised by BLAST searching techniques. The pathway shows that isoprenoid production in H. volcanii utilises the mevalonate pathway. The first two carotenogenic enzymes, phytoene synthase (CrtB2) and phytoene desaturase (CrtI) were modelled, and investigated, results indicating a possibility that they are membrane bound. A method for extraction, separation and quantification of the carotenoids of H. volcanii was developed. This approach used phase extraction of an aqueous and an organic layer, followed by HPLC separation of the extractant components and analysis by comparison of peak absorption at 450nm of the carotenoid being studied to a beta-carotene internal standard. This method was used to assess lycopene and phytoene levels throughout growth of the organism and under stress conditions. It was found that lycopene and phytoene are both synthesised at elevated levels in stationary phase growth. Additionally lycopene and phytoene levels show a response to oxidative stress, though not to other stressors, being degraded then accumulating to levels higher than found under none stress conditions. In order to gain insight into the function of lycopene in the organism the gene crtI coding for phytoene desaturase was deleted. This mutant was found to have all carotenoid production eliminated from the cell. This suggests that the carotenogenic enzymes may form a complex associated with the membrane. The mutant was subjected to stress conditions, the results showing it was highly susceptible to oxidative attack. This study suggests that the carotenoids synthesised by H. volcanii are vital to its defence against reactive oxygen species (ROS).